Six and 12 Weeks of Caloric Restriction Increases β Cell Function and Lowers Fasting and Postprandial Glucose Concentrations in People with Type 2 Diabetes. Issue 9 (5th August 2015) - Sathananthan, Matheni; Shah, Meera; Edens, Kim L; Grothe, Karen B; Piccinini, Francesca; Farrugia, Luca P; Micheletto, Francesco; Man, Chiara Dalla; Cobelli, Claudio; Rizza, Robert A; Camilleri, Michael; Vella, Adrian
Abstract: Background: Caloric restriction alone has been shown to improve insulin action and fasting glucose metabolism; however, the mechanism by which this occurs remains uncertain. Objective: We sought to quantify the effect of caloric restriction on β cell function and glucose metabolism in people with type 2 diabetes. Methods: Nine subjects (2 men, 7 women) with type 2 diabetes [BMI (in kg/m 2 ): 40.6 ± 1.4; age: 58 ± 3 y; glycated hemoglobin: 6.9% ± 0.2%] were studied using a triple-tracer mixed meal after withdrawal of oral diabetes therapy. The oral minimal model was used to measure β cell function. Caloric restriction limited subjects to a pureed diet (<900 kcal/d) for the 12 wk of study. The studies were repeated after 6 and 12 wk of caloric restriction. Results: Fasting glucose concentrations decreased significantly from baseline after 6 wk of caloric restriction with no further reduction after a further 6 wk of caloric restriction (9.8 ± 1.3, 5.9 ± 0.2, and 6.2 ± 0.3 mmol/L at baseline and after 6 and 12 wk of caloric restriction, respectively; P = 0.01) because of decreased fasting endogenous glucose production (EGP: 20.4 ± 1.1, 16.2 ± 0.8, and 17.4 ± 1.1 μmol · kg −1 · min −1 at baseline and after 6 and 12 wk of caloric restriction, respectively; P = 0.03). These changes were accompanied by an improvement in β cell function measured by the disposition index (189 ± 51, 436 ± 68, and 449 ± 67 10 −14 dL · kg −1 · min −2 · pmol −1 at baseline and after 6 and 12 wk of caloric restriction, respectively; P = 0.01). Conclusions: Six weeks of caloric restriction lowers fasting glucose and EGP with accompanying improvements in β cell function in people with type 2 diabetes. An additional 6 wk of caloric restriction maintained the improvement in glucose metabolism. This trial was registered at clinicaltrials.gov as NCT01094054.